115 BARRIERS AND FACILITATORS TO DOCTORS DEPRESCRIBING FALL-RISK INCREASING DRUGS IN OLDER ADULTS. (25th October 2022) - Kalim, R; Ryder, S; Cunningham, C; McMahon, N
Abstract: Background: Some medicines are associated with falls in older adults and have been classified as Fall-Risk Increasing Drugs (FRIDs). Deprescribing FRIDs is one of several possible preventive measures to reduce falls risk [1]. The aim of this qualitative study was to explore the barriers and facilitators to doctors deprescribing FRIDs in hospitals. Methods: Doctors, who were experienced in caring for older patients, were interviewed individually, directed by an interview guide, at a large teaching hospital. Thematic analysis of transcribed audio recordings was undertaken in NVivo 12. Results: A total of eighteen doctors participated in the study. Barriers and facilitators were classified into three categories: factors related to the care setting, to doctors and to patients. Incomplete patient medical records, limited time during inpatient stay, poor communication between care providers, and difficulties following up patients after discharge were major barriers to deprescribing in hospital. Doctors' barriers included concerns about consequences and reluctance changing medications initiated by other prescribers. Acute illness or resistance to change were patient-related barriers to deprescribing. Facilitators included doctors' awareness of the importance of deprescribing FRIDs, the ability to monitor patients during their inpatient stay, the use of electronic medical records, and support from other healthcare professionals e.g. clinical pharmacists. Conclusion: Deprescribing FRIDs in older adults is challenging. Interventions based on identified facilitators, such as improved communication between prescribers, enhanced documentation using electronic medical records, and the support of team members with expertise in medication review, might enhance the feasibility of deprescribing. Reference: 1. Seppala LJ et al. EuGMS Task and Finish group on Fall-Risk-Increasing Drugs (FRIDs): Position on Knowledge Dissemination, Management, and Future Research. Drugs Aging . 2019; 36(4): 299–307.